Establishment and Characterization of Primary Cultures from Iranian Oral Squamous Cell Carcinoma Patients by Enzymatic Method and Explant Culture - Meysam Ganjibakhsh; Pouyan Aminishakib; Parvaneh Farzaneh; Abbas Karimi; Seyed Abolhassan Shahzadeh Fazeli; Moones Rajabi; Ahmad Nasimian; Fereshteh Baghaei Naini; Hedieh Rahmati; Neda sadat Gohari; Nazanin Mohebali; Masoumeh Asadi; et al. (Frontiers in Dentistry, 2017)
Objectives: Oral Squamous Cell Carcinoma (OSCC) is the most frequent oral cancer worldwide. It is known as the eighth most common cancer in men and as the fifth most common cancer in women. Cytogenetic and biochemical studies in recent decades have emphasized the necessity of providing an appropriate tool for such researches. Cancer cell culture is a useful tool for investigations on biochemical, genetic, molecular and immunological characteristics of different cancers, including oral cancer. Here, we explain the establishment process of five primary oral cancer cells derived from an Iranian population. Materials and Methods: The specimens were obtained from five oral cancer patients. Enzymatic, explant culture and magnetic-activated cell sorting (MACS) methods were used for cell isolation. After quality control tests, characterization and authentication of primary oral cancer cells were performed by short tandem repeats (STR) profiling, chromosome analysis, species identification, and monitoring the growth, morphology and the expression of CD326 and CD133 markers. Results: Five primary oral cancer cells were established from an Iranian population. The flow cytometry results showed that the isolated cells were positive for CD326 and CD133 markers. Furthermore, the cells were free from mycoplasma, bacterial and fungal contamination. No misidentified or cross-contaminated cells were detected by STR analysis. Conclusions: Human primary oral cancer cells provide an extremely useful platform for studying carcinogenesis pathways of oral cancer in Iranian population. They may be helpful in explaining the ethnic differences in cancer biology and the individuality in anticancer drug response in future studies.